POTENTIAL RISKS AND PROBLEMS IN THE CULTIVATION OF PERENNIAL ENERGY CROPS - Dželetović, Željko; Andrejić, Gordana; Simić, Aleksandar; Geren, Hakan; Aleksić, Uroš; Brajević, Snežana (Journal on Processing and Energy in Agriculture, 2022)
Second-generation biofuel production systems are significantly better than first-generation systems. However, the size of areas on which the energy crops are grown depends on public support, and it decreases if the public support is missing. Despite all the environmental and economic benefits, perennial energy crops do not currently play a significant role. It is believed that available land areas will be a basic limiting factor for cultivating biofuel crops in the EU. On the other hand, there is significant untapped potential for bioenergy production in abandoned and marginal land in Southeast Europe. At the same time, perennial energy crops are investments with certain risks. Economically viable production of dedicated energy crops will be difficult to achieve on most lands classified into V-VIII land capability classes. In terms of the risk of farming investments, maize has an advantage over all perennial energy crop systems. We have identified 10 types of risks for successful production of energy crops: (1) Crop water supply; (2) Weed infestation in crops; (3) Risks of frost damages; (4) Crop lodging; (5) Crop diseases and pests; (6) Short harvest periods and variable yields; (7) Economic viability of cultivation on land areas of lower land capability class; (8) Influences of agricultural practices and agro-ecological conditions on biomass quality; (9) Storage of harvested biomass and fire hazard; and (10) economic sanctions, war and war surroundings. Although the cultivation of perennial energy crops has a perspective, it does must be systematically planned and further improved.
Keywords: energy crops; marginal land; land capability classes; production risks